(untitled) (Bangladesh Journal of Pharmacology, 2010)
The essential oils were isolated by hydrodistillation from the aerial parts of Adenosma capitatum and Limnophila aromatica and were analyzed by gas chromatography mass spectrometry (GC-MS). Forty six and thirty components were identified, representing 98.8% and 99.3% of the total oils respectively. Oil of A. capitatum rich in limonene (24.74%), fenchone (21.59%) and 2-carene (17.64%). On the other hand, L. aromatica rich in Z-ocimene (39.21%), terpinolene (17.24%) andcamphor (12.89%).